Il discorso di Eraclito Un modello semantico e cosmologico - Gianvittorio, Laura (Georg Olms Verlag, 2010)
Since the "scuola urbinate" (e. g. B. Gentili) applied the oral theory to the Greek lyricists, orality is seen to have influenced thought and language not only of rhapsodists, but of archaic authors in general. Against this background, I investigate how the interaction between orality and literacy, which I suggest to call "aurality", influences the semantics and the linguistic reasoning chiefly of Heraclitus among the early presocratic thinkers. On the one hand Heraclitus is an oral "image-thinker" (Havelock) and his prose is poetically constructed; on the other hand only by writing he can figure out the discourse (λόγος) as a ὀνόματα-composed unity, as I mean he does, rather than holistic or as a continuum, what is common in oral societies. Such a λόγος is able to serve as a cosmological model, for the physical world consisting of a multiplicity of phenomena closely jointed to each other into an invisible unity.